An Analysis Of The Influence Of Leadership Style, Work Motivation, And Compensation On Employee Performance At PT Perkebunan Nusantara III (Persero) Medan - Michael Hamberson Sipahutar; Siswa Pratama; Wilchan Robain (Jurnal Fokus Manajemen, 2026)
This study aims to examine the effects of compensation, leadership style, and work motivation on employee performance. A quantitative approach with a survey method was employed. The research population consisted of all employees at the study object, and a census sampling technique was applied, resulting in 60 respondents. Data were collected through questionnaires and analyzed using multiple linear regression with the assistance of SPSS software. The results indicate that compensation, leadership style, and work motivation simultaneously have a significant effect on employee performance. Partially, leadership style and work motivation significantly affect employee performance, while compensation does not show a significant effect. The coefficient of determination reveals that the contribution of the independent variables to employee performance is relatively limited, suggesting that other factors beyond the research model also influence employee performance. These findings imply that improving employee performance requires a greater emphasis on effective leadership practices and the enhancement of work motivation.